OP0255 Clinical Characteristics of Infections in Connective Tissue Diseases (CTD); Association with Glucocorticoids (GC) and Glucose Intolerance. (10th June 2014) - Kuda, H.; Ushikubo, M.; Ito, H.; Izumi, K.; Akiya, K.; Tamaki, S.; Tanaka, I.; Oshima, H.
Abstract : Background: Patients with connective tissue diseases (CTD) have an increased risk for infectious disease-related morbidity and mortality. This risk in due in part to the underlying immune cell dysfunction and the immunosuppressive therapies. In the past decade a number of newly developed biologic therapies have delivered clinical benefits to CTD patients. With these therapies, however, CTD patients have now more risks for the serious bacterial and opportunistic infections. Objectives: To investigate clinical characteristics of infections in CTD, especially co-relation with glucocorticoids or glucose intolerance. Methods: We retrospectively reviewed the medical records of all patients with CTDs visited at the Department of Connective Tissue Diseases, Tokyo Medical Center, Tokyo, Japan, between April 1, 2006, and March, 31, 2013. Results: A total of 2893 patients visited the office during 8-years study period. Of these, 1170 patients followed for more than half a year were reviewed. Mean age was 63.9 years. They were followed up for a mean of 830 days. There were 177 patients (13.4%) with infections (respiratory infection in 36.4%, urinary tract infection in 26.5%, skin infection in 17.4%). Serious infection (SIE) were seen in 33%. Prednisolone (PSL) was used in 74% of patients with infections and 54% without infections, Immunosuppressants were used in 29% of patients with infections and 18% without infection, Biologics used in 5% with infection and in 2% without infection (p<0.01-0.05). A frequency of commodities (diabetes mellitus, chronic renal disease (CKD), chronic lung disorders) was higher in patients with infections than without infections (p<0.01-0.05). Multiple regression analysis revealed that risk factors of infections in CTD were PSL use, increased age, CKD, chronic lung disorders (p<0.01-0.05). Total dose of PSL in 6 months was positively correlated with the rate of infections (p<0.01). Age, HbA1c and total dose of PSL in 6 months were significantly higher in patients with SIEs than in non-SIEs (p<0.01). Conclusions: Patients with CTD had high risk of developing infections. Especially patients with diabetes mellitus, CKD, chronic lung disorders and higher age had increased risk of infectious diseases. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2929